A critical appraisal of randomized controlled trials on intravenous phenytoin in convulsive status epilepticus. (24th January 2018) - Brigo, F.; Bragazzi, N. L.; Lattanzi, S.; Nardone, R.; Trinka, E.
Abstract : Since the 1970s, intravenous (IV) phenytoin (PHT) has traditionally been used as second‐stage treatment for convulsive status epilepticus (SE) after failure of benzodiazepines. The aim of this review was to critically assess the evidence supporting the use of IV PHT as treatment of convulsive SE in patients of any age. In particular, we critically appraised the results of randomized controlled trials (RCTs) evaluating IV PHT as treatment of convulsive SE. A systematic search of the literature was carried out to identify RCTs evaluating IV PHT as treatment of convulsive SE in patients of any age. Eight RCTs (544 patients allocated to IV PHT) were included. The included studies differed in almost every single characteristic considered. Six RCTs (472 patients) used IV PHT without demonstrating refractoriness of SE to benzodiazepines. Only two RCTs (72 patients) used IV PHT as second‐line treatment for benzodiazepine‐resistant convulsive SE. Overall, most evidence from RCTs supports the use of IV PHT immediately after IV diazepam, even if seizures have not recurred. The recommendation derived from RCTs supporting the use of IV PHT as second‐line treatment in benzodiazepine‐resistant convulsive SE is weak. This is emblematic of the lack of robust evidence from large RCTs to inform clinical practice on how to treat SE after failure of first‐line drugs. IV PHT given immediately after first‐line benzodiazepines could prolong their short antiepileptic effect and prevent seizure recurrence.